2018
DOI: 10.1113/jp276720
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic entrainment of ectopic action potential generation in hippocampal pyramidal neurons

Abstract: While most action potentials are generated at the axon initial segment, they can also be triggered at more distal sites along the axon. Such ectopic action potentials (EAPs) occur during several neuronal pathologies such as epilepsy, nerve injuries and inflammation but have also been observed during physiological network activity. EAPs propagate antidromically towards the somato-dendritic compartment where they modulate synaptic plasticity. Here we investigate the converse signal direction: do somato-dendritic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Neuroinflammation has been determined as both the cause and the result of epilepsy (Barker-Haliski et al, 2017), and is a promoter of epileptogenesis (Vezzani et al, 2016). Many studies have confirmed that inflammatory mediators and cytokines such as IL-1β can mediate neuronal cell loss (Varvel et al, 2016), contribute to related molecular and synaptic plasticity (Thome et al, 2018), and affect synaptic transmission and neuronal excitability (Vezzani and Viviani, 2015), thereby promoting epileptogenesis, and ultimately leading to seizures and recurrence (Vezzani et al, 2015). Amentoflavone affects the production of inflammatory mediators including inducible cyclooxygenase-2 (COX-2), nitric oxide synthase (NOS), TNF-α, and IL-6, which are mediated by NF-κB signal transduction pathways (Sakthivel and Guruvayoorappan, 2013; Yen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation has been determined as both the cause and the result of epilepsy (Barker-Haliski et al, 2017), and is a promoter of epileptogenesis (Vezzani et al, 2016). Many studies have confirmed that inflammatory mediators and cytokines such as IL-1β can mediate neuronal cell loss (Varvel et al, 2016), contribute to related molecular and synaptic plasticity (Thome et al, 2018), and affect synaptic transmission and neuronal excitability (Vezzani and Viviani, 2015), thereby promoting epileptogenesis, and ultimately leading to seizures and recurrence (Vezzani et al, 2015). Amentoflavone affects the production of inflammatory mediators including inducible cyclooxygenase-2 (COX-2), nitric oxide synthase (NOS), TNF-α, and IL-6, which are mediated by NF-κB signal transduction pathways (Sakthivel and Guruvayoorappan, 2013; Yen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In their study, the authors showed that coupling is stronger in the orthodromic than in the antidromic direction, and they attributed this effect to the impedance mismatch between the two compartments: the input resistance being much lower in the soma, an axonally injected current will induce a strong local (i.e., axonal) voltage change and a much smaller somatic voltage change. As pointed out by Thome et al (2018), who showed a similar asymmetric coupling between the axonal and the somatic compartment of hippocampal pyramidal neurons, the input capacitance of each compartment will also have a kinetic effect: the higher the capacitance (soma), the slower will be the voltage change; the smaller the capacitance (axon), the quicker the voltage change will be.…”
Section: The Axonal Length Constant “λ”mentioning
confidence: 83%
“…In a recent paper, Thome et al (2018) showed that EAPs (probably the spikelets in Epsztein’s work) can be triggered in hippocampal CA1 pyramidal neurons by axonal stimulation. In their paper, the authors showed that EAPs reliably propagate toward the soma, and further showed that their occurrence can be modulated by subthreshold synaptic activity, either depolarizing or hyperpolarizing, in the somatodendritic compartment.…”
Section: The Case Of Ectopic Activitymentioning
confidence: 99%
“…In this issue of The Journal of Physiology , Thome and coworkers () have answered this question by showing that spontaneous or evoked synaptic activity generated in the somato‐dendritic compartment is transmitted with little attenuation (∼20%) and over long distances (>300 μm) in axons of CA1 pyramidal cells (Thome et al ., ). Voltage transients were even amplified in the proximal region of the axon.…”
mentioning
confidence: 99%
“…Next, Thome et al examined the role of evoked excitatory and inhibitory synaptic potentials in the generation of EAPs. The probability of evoking an EAP by extracellular stimulation of the alveus was greatly enhanced when EPSPs were evoked simultaneously (Thome et al, 2018). In contrast, EAPs were less successful when inhibitory postsynaptic potentials (IPSPs) were evoked with an extracellular stimulating electrode located near the soma.…”
mentioning
confidence: 99%